Serum magnesium level and its relationship with internal medium in incident patients attending an emerging service of a public hospital - Barrios Juárez, Luis Enrique (2019)
Serum magnesium participates in multiple metabolic processes; several studies have shown that alterations in its serum levels are associated with chronic illnesses, alterations in the internal medium and the critical care units these alterations are associated with higher mortality. Objectives: To determine the relationship between serum magnesium level and alterations in the internal medium in incident patients attending an emerging service of a public hospital. Methods: 201 patients were included who had measurements of serum magnesium, creatinine, serum electrolytes and blood gases on admission to the emergency room at Hospital Cayetano Heredia (CHH) between 2017-2018. Results: Mean age was 60.1 ± 20.1 years. Mean serum magnesium level was 2.05 ± 0.57 mg/dl. Hypo and hypermagnesemia were observed in 20.4% and 21.9%, respectively. Bivariate lineal analysis showed correlation of magnesium with creatinine, potassium, phosphorus, pH and bicarbonate. The multiple lineal regression showed association of magnesium with pH only, which was corroborated in the stratified analysis, no association with age, gender and clinical variables was found. Conclusions: Serum magnesium levels are frequently altered in patients attending the emergency room at CHH and correlates with bicarbonate, creatinine, potassium, phosphorus and pH, with the latter being more relevant.